Increased expression of CYP17A1 indicates an effective targeting of the androgen receptor axis in castration resistant prostate cancer (CRPC) - Bremmer, Felix (Springer International Publishing, 2014)
Recent breakthrough therapies targeting androgen receptor signalling in castration resistant prostate cancer (CRPC) involve multifunctional androgen receptor (AR) blockade and exhaustive androgen deprivation. Nevertheless, limitations to an enduring effectiveness of new drugs are anticipated in resistance mechanisms occurring under such treatments. In this study we used CRPC cell models VCaP and LNCaP as well as AR-negative PC-3- and non-neoplastic epithelial BPH-1-cells treated with 5, 10 or 25 μmol/L abiraterone hydrolyzed from abiraterone acetate (AA). The origin of CYP17A1 up-regulation under AA treatment was investigated in CRPC cell models by qRT-PCR and western-blot procedures. AA treatments of AR positive CRPC cell models led to decreased expression of androgen regulated genes such as PSA. In these cells diminished expression of androgen regulated genes was accompanied by an up-regulation of CYP17A1 expression within short-term treatments. No such effects became evident in AR-negative PC-3 cells. AR directed siRNA (siAR) used in VCaP cells significantly reduced mRNA expression and AR protein abundance. Such interference with AR signalling in the absence of abiraterone acetate also caused a marked up-regulation of CYP17A1 expression. Down-regulation of androgen regulated genes occurs in spite of an elevated expression of CYP17A1, the very target enzyme for this drug. CYP17A1 up-regulation already takes place within such short treatments with AA and does not require adaptation events over several cell cycles. CYP17A1 is also up-regulated in the absence of AA when AR signalling is physically eliminated by siAR. These results reveal an immediate counter-regulation of CYP17A1 expression whenever AR-signalling is inhibited adequately but not a persisting adaptation yielding drug resistance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2193-1801-3-574) contains supplementary material, which is available to authorized users.